2016
DOI: 10.1080/01694243.2016.1204144
|View full text |Cite
|
Sign up to set email alerts
|

Effect of material and fabrication technique on marginal fit and fracture resistance of adhesively luted inlays made of CAD/CAM ceramics and hybrid materials

Abstract: This study evaluated the fracture resistance and marginal fit of CAD/CAM ceramic and composite inlays. Molars (N = 80) were prepared to receive Mesio-occlusal-distal (MOD) inlays and randomly divided into four groups to be restored depending on the materials: (a) HLD: heat-pressed lithium disilicate ceramic (IPS e.max Press), (b) CLD: CAD/CAM-fabricated lithium disilicate ceramic (IPS e.max CAD), (c) NC: CAD/CAM nano-ceramic resin (Lava Ultimate), (d) RC: Indirect resin composite (Filtek P60). Each group was r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
44
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(47 citation statements)
references
References 47 publications
(73 reference statements)
2
44
1
Order By: Relevance
“…These findings were confirmed by Yamaner et al (23) who stated that the higher fracture force of CAD/CAM restorations may be the result of optimized industrial manufacturing conditions and subsequent minimal voids and volume defects.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…These findings were confirmed by Yamaner et al (23) who stated that the higher fracture force of CAD/CAM restorations may be the result of optimized industrial manufacturing conditions and subsequent minimal voids and volume defects.…”
Section: Discussionsupporting
confidence: 79%
“…Yamaner et al (23) studied the effect of material type and fabrication technique on fracture resistance of adhesively luted inlay restorations. It was concluded that CAD/CAM-fabricated lithium disilicate ceramic inlays have higher fracture resistance values compared to heat-pressed fabricated lithium disilicate ceramic.…”
Section: Introductionmentioning
confidence: 99%
“…The developments of CAD/ CAM technology combined with the new ceramic materials specifically designed for this technology are attracting the curiosity of many researchers. 5,9,10,[29][30][31] The principles of chair-side CAD/CAM are becoming increasingly accepted among clinicians and universities, changing the common way of learning indirect restorations and providing access to their application by more professionals in their practices. 10,32,33,34 A new skill is becoming of major importance for future dentists, improving their competence and ability to do digital restorations.…”
Section: Discussionmentioning
confidence: 99%
“…The factors that are not easy to predict are tool wear, chipping control, machining and energy forces, and surface finish and integrity, because they can be checked only after manufacturing and qualitatively analyses. 9,10,29 Due to application of the modern way of manufacturing ceramic restorations, quantitative analysis is extremely necessary to assess the purpose of new materials.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation